2015
DOI: 10.1111/odi.12364
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacteria in placental tissues: increased molecular detection in pregnant periodontitis patients

Abstract: These results, along with previous findings, show that oral bacteria may be normally present in the placenta, however, the levels of certain oral pathogens in the placenta would highly depend on the mother's periodontal state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 53 publications
2
33
0
5
Order By: Relevance
“…In a similar vein, microbes -presumably persistent, dormant organisms -are regularly detected in other tissues in which any degree of proliferation would be highly inimical to the host. Some recent examples involving just reproductive disorders include the vagina, [523][524][525] the placenta, [526][527][528][529][530] and the amniotic fluid, [531][532][533][534][535][536][537][538][539][540] while recent evidence has also been provided for a sub-epidermal microbiome. 541 The considerable evidence for a dormant CNS microbiome was discussed earlier, and we here note the presence in the brain of TLR4 and its major role in neurodegeneration, 542 consistent with the idea that waking up dormant microbes can stimulate overt neurodegenerative disease.…”
Section: Differences In the Tissue Locations Of Dormant Bacteriamentioning
confidence: 99%
“…In a similar vein, microbes -presumably persistent, dormant organisms -are regularly detected in other tissues in which any degree of proliferation would be highly inimical to the host. Some recent examples involving just reproductive disorders include the vagina, [523][524][525] the placenta, [526][527][528][529][530] and the amniotic fluid, [531][532][533][534][535][536][537][538][539][540] while recent evidence has also been provided for a sub-epidermal microbiome. 541 The considerable evidence for a dormant CNS microbiome was discussed earlier, and we here note the presence in the brain of TLR4 and its major role in neurodegeneration, 542 consistent with the idea that waking up dormant microbes can stimulate overt neurodegenerative disease.…”
Section: Differences In the Tissue Locations Of Dormant Bacteriamentioning
confidence: 99%
“…Also confounding is that P. gingivalis DNA or antigen has also been detected in placentas from healthy pregnancies, albeit at a lower microbial load and lower frequency than women with preeclampsia or preterm birth [3][4][5][6][7]. It is also difficult to extrapolate the contribution P. gingivalis to APO when its detection in utero-placental tissues is usually in association with other oral bacterial species [3][4][5], or when it is not detected in placental tissues from complicated pregnancies even when other oral bacterial species are present [13].…”
Section: Introductionmentioning
confidence: 96%
“…Experimental infection in various animal models confirms that invasion of the uterine compartment by P. gingivalis produces a diverse array of APO, including utero-placental pathology, enhanced expression of pro-T helper (TH)1 type cytokines (IFN-γ, IL-2, IL-12, and TNF-α), fetal growth restriction (FGR), and spontaneous preterm delivery [12][13][14][15]. Since these outcomes are manifestations of different pathologic mechanisms within the fetal compartment, it may seem somewhat perplexing that one organism could be responsible for all of these complications.…”
Section: Introductionmentioning
confidence: 99%
“…The most ubiquitous bacterium, Fusobacterium nucleatum, was more prevalent in mothers with periodontitis and preterm births and/or low birthweight neonates. Porphyromonas gingivalis, Treponema denticola, Prevotella intermedia and Aggregatibacter actinomycetemcomitans were not detected [23].…”
Section: Pathogens Involved In Pdmentioning
confidence: 92%
“…Actinomyces infections in pregnancy are rare but, if they occur, have been linked primarily with preterm deliveries [22]. Blanc et al [23] found the placentas from women with periodontitis showed a higher prevalence of periodontopathogens compared to those from women without periodontitis. Samples showed low prevalences of Actinomyces israelii, Parvimonas micra and Tannerella forsythia.…”
Section: Pathogens Involved In Pdmentioning
confidence: 99%